CB3E2q (q = ±1): a family of "hyparene" analogues with a planar pentacoordinate carbon. Issue 18 (26th April 2018) - Liu, Ping; Bian, Jian-Hong; Wang, Qiang; Huang, Fang; Li, Debao; Wu, Yan-Bo
Abstract : Highlighted elements are the feasible E atoms of CB3 E2 q template ppC structures, in which CB3 Mg2 − is suitable for photoelectron spectroscopy. Abstract : A CB3 moiety extracted from the building units of milestone "hyparenes" (families of species with a planar pentacoordinate carbon (ppC)) was found to be a more basic building block, which can be employed to design a family of "hyparene" analogues CB3 E2 q ( q = ±1) also with a ppC. The majority of main group elements can feasibly serve as the E atom. Despite the number of valence electrons, the ppC atoms in the CB3 E2 q ( q = ±1) species were involved in three delocalized σ orbitals and a delocalized π orbital, so the carbon atom obeys the octet rule. The NICS studies indicated that these ppC structures are σ and π double aromatic. Given that most of them are less favourable in energy than their boron-centered isomers, it is remarkable that the global minimum of CB3 Mg2 − adopts the ppC arrangement. Such a ppC structure is also kinetically stable. Compared to previously reported anionic ppC global minima, CB3 Mg2 − does not contain hyper toxic beryllium and thus is much more attractive to our experimental colleagues for realizing the ppC species using negative ion photoelectron detachment spectroscopy.